Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Identifying a System with No Solution

Which system has no solution?

A.
[tex]\[
\begin{array}{c}
y=-3x+8 \\
6x+2y=-4.5
\end{array}
\][/tex]

B.
[tex]\[
\begin{array}{r|r}
y=9x+6.25 & y=4.5x-5 \\
-18x+2y=12.5 & -3x+2y=6
\end{array}
\][/tex]

C.
[tex]\[
\begin{array}{c}
y=3x+9 \\
x+8y=12.3
\end{array}
\][/tex]


Sagot :

To solve the problem of identifying which system of equations has no solution, let's analyze each system individually:

### System 1:
[tex]\[ \begin{cases} y = -3x + 8 \\ 6x + 2y = -4.5 \end{cases} \][/tex]
1. Substitute [tex]\( y \)[/tex] from the first equation into the second equation:
[tex]\[ 6x + 2(-3x + 8) = -4.5 \][/tex]
2. Simplify inside the parentheses:
[tex]\[ 6x - 6x + 16 = -4.5 \][/tex]
3. Combine like terms:
[tex]\[ 16 \neq -4.5 \][/tex]
This statement is false. Therefore, there is no value of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that can satisfy both equations simultaneously. Hence, System 1 has no solution.

### System 2:
[tex]\[ \begin{cases} y = 9x + 6.25 & y = 4.5x - 5 \\ -18x + 2y = 12.5 & -3x + 2y = 6 \end{cases} \][/tex]
1. Set the two [tex]\( y \)[/tex] equations equal to each other to find [tex]\( x \)[/tex]:
[tex]\[ 9x + 6.25 = 4.5x - 5 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
[tex]\[ 9x - 4.5x = -5 - 6.25 \\ 4.5x = -11.25 \\ x = -2.5 \][/tex]
3. Substitute [tex]\( x \)[/tex] into either [tex]\( y \)[/tex] equation to find [tex]\( y \)[/tex]:
[tex]\[ y = 9(-2.5) + 6.25 = -22.5 + 6.25 = -16.25 \][/tex]
Since we can find specific values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy the equations, System 2 has solutions.

### System 3:
[tex]\[ \begin{cases} y = 3x + 9 \\ x + 8y = 12.3 \end{cases} \][/tex]
1. Substitute [tex]\( y \)[/tex] from the first equation into the second equation:
[tex]\[ x + 8(3x + 9) = 12.3 \][/tex]
2. Simplify inside the parentheses:
[tex]\[ x + 24x + 72 = 12.3 \][/tex]
3. Combine like terms and solve for [tex]\( x \)[/tex]:
[tex]\[ 25x + 72 = 12.3 \\ 25x = 12.3 - 72 \\ 25x = -59.7 \\ x = -2.388 \][/tex]
4. Substitute [tex]\( x \)[/tex] into the first equation to find [tex]\( y \)[/tex]:
[tex]\[ y = 3(-2.388) + 9 = -7.164 + 9 = 1.836 \][/tex]
Since we can find specific values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy these equations, System 3 has solutions.

### Conclusion
The system that has no solution is System 1:
[tex]\[ \begin{cases} y = -3x + 8 \\ 6x + 2y = -4.5 \end{cases} \][/tex]